1996
DOI: 10.1021/ie950502z
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and Mechanism of Anodic Oxidation of n-Butanol by Nickel Peroxide

Abstract: A detailed mechanism of indirect oxidation of n-butanol by using NiO(OH) as the mediator has been proposed. After NiO(OH), a kind of nickel peroxide, abstracts a hydrogen atom from n-butanol to form RC•HOH free radical, indirect and direct oxidation paths may occur, and the indirect oxidation path is preferred to the direct electrooxidation path. From the theoretical analysis, when the applied potential is lower than 0.550 V (vs Ag/AgCl), the apparent current shows first-order dependence on both the hydroxide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Nickel electrodes can be applied for electrochromic devices, 1) alkaline batteries 2) and as electrocatalysts. 3,4) Most of these applications are originated based on the redox pair system Ni (OH) 2 /NiOOH 5,6) At a potential range of less than 0.6 V, nickel dissolves from the nickel electrode surface. 7) Nickel plating is carried out either by electroplating method or electroless plating techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Nickel electrodes can be applied for electrochromic devices, 1) alkaline batteries 2) and as electrocatalysts. 3,4) Most of these applications are originated based on the redox pair system Ni (OH) 2 /NiOOH 5,6) At a potential range of less than 0.6 V, nickel dissolves from the nickel electrode surface. 7) Nickel plating is carried out either by electroplating method or electroless plating techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Nickel electrodes have been applied to an electrochromic device [8], alkaline battery [9], and as a electrocatalyst [10,11]. Most of the applications are on the basis of the redox pair, Ni(OH) 2 aNiOOH [12,13]. Casella et al reported the applications of a nickel chemical modi®ed electrode (Ni-CME) to detect aliphatic alcohols [14].…”
Section: Introductionmentioning
confidence: 99%
“…There is great scientific and technological interest in the study of nickel-based materials, which are applied as an electrocatalyst for organic synthesis [1][2][3] or as sensors for alcohol detection. [4][5][6][7][8] The oxidation of alcohol is based on the redox pair Ni(OH) 2 /NiOOH, which can be formed on the nickel surface in alkaline medium.…”
mentioning
confidence: 99%